Equity Valuation of Heineken N.V. - Sousa, Raquel Alexandra Matos de (2023)
In this dissertation, Heineken’s fair value per share, as of 31st December 2024 was estimated and compared with its actual market share price, as of 31st March 2023. Hereby, this thesis aims to provide an investment recommendation, of whether to buy, hold or sell a stock position in the company, in relation with the market price. By first studying the different commonly used valuation models, the WACCbased DCF was selected as the main and most suitable one for valuing Heineken. Moreover, a relative valuation was also performed in order to compare the results obtained with the DCF analysis. The DCF valuation delivered a target share price of €136.4. This obtained target share price, in comparison with the actual market share price of €99.1, as of 31st March 2023, results in an estimated upside potential of +37.6%. Hence, a Buy recommendation to Heineken’s share is recommended. The outputs obtained from the relative valuation also supported this recommendation. Finally, the conclusions and assumptions used in this thesis were compared with the ones from an equity investment report, J.P.Morgan. The results between both and respective investment recommendation differed, as J.P.Morgan obtained a target share price of €100, as of 31st December 2024, providing a neutral recommendation. The different fair prices are the reflection of different assumptions made in the computations of certain forecasts, between this dissertation and J.P.Morgan, as the last presented a more conservative position.